Environmental constraints and call evolution in torrent‐dwelling frogs. (4th April 2016) - Goutte, Sandra; Dubois, Alain; Howard, Samuel D.; Marquez, Rafael; Rowley, Jodi J. L.; Dehling, J. Maximilian; Grandcolas, Philippe; Rongchuan, Xiong; Legendre, Frédéric
Abstract : Although acoustic signals are important for communication in many taxa, signal propagation is affected by environmental properties. Strong environmental constraints should drive call evolution, favoring signals with greater transmission distance and content integrity in a given calling habitat. Yet, few empirical studies have verified this prediction, possibly due to a shortcoming in habitat characterization, which is often too broad. Here we assess the potential impact of environmental constraints on the evolution of advertisement call in four groups of torrent‐dwelling frogs in the family Ranidae. We reconstruct the evolution of calling site preferences, both broadly categorized and at a finer scale, onto a phylogenetic tree for 148 species with five markers (∼3600 bp). We test models of evolution for six call traits for 79 species with regard to the reconstructed history of calling site preferences and estimate their ancestral states. We find that in spite of existing morphological constraints, vocalizations of torrent‐dwelling species are most probably constrained by the acoustic specificities of torrent habitats and particularly their high level of ambient noise. We also show that a fine‐scale characterization of calling sites allows a better perception of the impact of environmental constraints on call evolution.